To morphological description of cardiovascular system in pinnipeds (Pinnipedia) - Alexey E. Kuzin (Известия ТИНРО, 2015)
Morphometric parameters of the heart, the absolute and relative caliber of the aortic arch and the major arterial trunks are determined for northern fur seal Callorhinus ursinus , Steller sea lion Eumetopias jubatus , spotted seal Phoca largha , harbor seal Phoca vitulina stejnegeri , and ribbon seal Histriophoca fasciata . The value of cardiac index, the thickness of ventricular wall, and the relative diameter of arterial trunks correlate well with energy expenditures of the entire body of mammals or their certain organs during the life cycle. The hypothesis is confirmed on seals’ adaptation to asphyxia by pronounced dilatation of the aorta ascending that ensures constant blood pressure and supports perfusion of brain and cardiac tissue.